Response of thermoelastic micropolar cubic crystal under dynamic load at an interface - Ailawalia, Praveen; Sachdeva, Sunil Kumar; Pathania, Devinder Singh (Zielona Góra: Uniwersytet Zielonogórski)
The purpose of this paper is to study the two dimensional deformation in a thermoelastic micropolar solid with cubic symmetry. A mechanical force is applied along the interface of a thermoelastic micropolar solid with cubic symmetry (Medium I) and a thermoelastic solid with microtemperatures (Medium II). The normal mode analysis has been applied to obtain the exact expressions for components of normal displacement, temperature distribution, normal force stress and tangential coupled stress for a thermoelastic micropolar solid with cubic symmetry. The effects of anisotropy, micropolarity and thermoelasticity on the above components have been depicted graphically.
Keywords: thermoelasticity; cubic symmetry; microtemperatures; normal mode